„VORES ØL“ Ajon og sociale relationer i Teso, Østuganda - Henriques, Peter (Tidsskriftet Antropologi, 1998)
Peter Henriques: Our Beer: Ajon and Social Relations among the Iteso, East Uganda When it comes to a description of Iteso community life and commensality, the first thing which comes to mind, both to the Iteso themselves and to outside observers, is the local beer, ajon. I claim here that the consumption of ajon is a way of practicing “the good life”, an ordered life where oppositions in the system of social and cultural reproduction are temporarily muted. Ajon drinking is presented here as mediating the ambivalence of good and evil found in all central social relations among Iteso. But if the consumption ideally is supposed to be only merry sociability, this sociability is under constant threat because of fear of people who might want to harm others. Ajon consumption can be dangerous, since the beer party is also a place where people, under cover of friendliness, may try to poison you or practice witchcraft.